Religion and British Raj Religious Development in Multan Division during Colonial Period - Majeed, Khuram; Abbas, Qaswar (Pakistan Languages and Humanities Review, 2023)
Like other regions and countries around the world, religion and religious development have remained an important aspect of South Asian culture. In some instances, people’s religious habits were thought to be the primary determinant of their identity. This article aims to comprehend and identify the fundamental theological tendencies that affected Multan’s division under British administration. South Asia in general and Multan in particular have seen a movement toward a diversity of religious views. Muslims, Sikhs, and Hindus were the most well-known and prominent religious groups that contributed to Multani culture. Christianity was the new religion that took off in Multan and other nearby locations. There were a few locals who converted to the new religion, but the number of conversions to the new infrastructure of religious buildings (churches), which became a part of Multani society, was not great. In this research study, only the materials that have been documented, both primary and secondary sources are used. According to the study’s findings, religious peace predated the arrival of the British and was a feature of society. However, as rulers changed and society and culture changed, a number of problems arose